Costs and optimisation options for monitoring of indirect dischargers. Issue 1 (2nd December 2021) - Franz, T.
Abstract: Monitoring of indirect and industrial dischargers, respectively, makes an important contribution to the safe and environmentally sound operation of wastewater systems. As a result of local framework conditions, there is a wide range of monitoring practices across Germany. In a benchmarking project, ten sewerage operators and monitoring bodies representing large German cities have collected data on their work and discussed their practices. The results show that the extent of monitoring is between 244 and 1, 457 monitoring points per sewer network (given as 15 th and 85 th percentile). The median value of the specific expense is 689 EUR per monitoring point and year. In relation to the total wastewater fee volume, the median expense is 0.71%. The sub-process 'sampling' was examined more closely. By means of detailed process mapping and regression analyses, it can be shown that on-site activities and tours have the largest share of working time (total of 72%) and thus the greatest leverage in optimisation measures. Various examples are given. HIGHLIGHTS: Current values of monitoring costs for industrial dischargers. Identified best practices for sampling.